A Case Report Of Oral Ulcer In Rheumatoid Arthritis: A Diagnostic And Management Dilemma - Siti Asmat Md Arepen; Dinie Qistina Rajalie; Azreen Zaira Abu Bakar; Nor Azirah Salahuddin; Nour Hanan Daniah Mohd Bakhit; Ahmad Anwaar Muhammad Saifullah; Nor Eyzawiah Hassan (Universiti Putra Malaysia; Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2024)
Malaysian Journal of Medicine and Health Sciences Volume 19 Issue (SUPP19) Page (31-33)